Zgodovina misli o jeziku na Slovenskem Katoliška doba (1600-1758) - Ahačič, Kozma (Linguistica et philologica, 2012)
In his treatise, the author shows that from the point of view of the history of linguistics and language use the transition from the Protestant to the Catholic period was not as sharp as one could conclude on the basis of some facts of cultural history. For a variety of reasons, the language tradition of Slovenian Protestant authors was preserved in the period in question. The author first indicates the directions the Slovenian language took in the Catholic period. The central part of the study is dedicated to the analysis of the grammars written in this period. The last part contains a critical edition and analysis of all linguistic comments on the Slovenian language in the Catholic period.